2018
DOI: 10.3390/su10093113
|View full text |Cite
|
Sign up to set email alerts
|

Value Migration to the Sustainable Business Models of Digital Economy Companies on the Capital Market

Abstract: The topic of a sustainable business model is currently the subject of much scientific research that covers a wide range of topics, from terminological aspects to aspects related to the impact of sustainability factors on company development. So far, however, the topic of sustainability in business models operating in electronic markets has only been studied to some extent. This article covers broad research into the value migration to sustainable business models of companies operating in the digital economy on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 48 publications
2
34
0
Order By: Relevance
“…To identify relevant articles and to build on (rather than replicate) the findings of a number of recent systematic review articles, we also required that the topic of business model innovation, digitization, and sustainability be dealt with in an essential way. This literature search generated articles on a research agenda for the circular economy and Industry 4.0 [40], sustainable business model archetypes [42,58], and canvas [27] or other conceptualizations-such as sufficiency-based business models [59], value migration [60], e-leadership in SMEs [61], success factors of peer-to-peer goods-sharing platforms [62], and a framework for analyzing the strategic potential of digitization in business model development, based on case-study evidence [63].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To identify relevant articles and to build on (rather than replicate) the findings of a number of recent systematic review articles, we also required that the topic of business model innovation, digitization, and sustainability be dealt with in an essential way. This literature search generated articles on a research agenda for the circular economy and Industry 4.0 [40], sustainable business model archetypes [42,58], and canvas [27] or other conceptualizations-such as sufficiency-based business models [59], value migration [60], e-leadership in SMEs [61], success factors of peer-to-peer goods-sharing platforms [62], and a framework for analyzing the strategic potential of digitization in business model development, based on case-study evidence [63].…”
Section: Methodsmentioning
confidence: 99%
“…Some argue that digital technologies have already created a virtual and autonomous economy that provides external intelligence in business [95]. Access to large datasets often determines market valuations of corporations [60]. However, algorithms need to be carefully checked for potential bias, as sadly shown by the case of a risk-assessment software, which made false predictions about black and white defendants [96].…”
Section: Optimization Technologiesmentioning
confidence: 99%
“…It is their continuous effort and sustainable job performance that contribute to company performance and thus drive business success. Based on a study of digital economy companies, Jabłoński observed that managers can be inspired to consider sustainability-related factors in their projects [78]. Managers in young firms should find ways to enhance workers' sustainable job performance by helping workers realize how their work contributes towards company's sustainability goals and find meaning in their work.…”
Section: Managerial Implicationsmentioning
confidence: 99%
“…The annual equity returns show the stock price change and the dividend payments over the period (Aebi et al, 2012). The literature has identified that digitalization (Jabłonski, 2018), and CS (Brammer et al, 2006) as sources of equity performance. In turn, the ratio of non-interest expenses to total net income (Lin and Zhang, 2009) is a proxy of banks' efficiency, a reduction meaning an efficiency improvement.…”
Section: Dependent Variablesmentioning
confidence: 99%